Iron Therapies For Iron Deficiency In Chronic Kidney Disease: A Literature Review - Zhela Fatin Fatiha; Nining Lestari; Aulia Nissa Rizky Hariyono; Tia Mella Citra; Ayu Mayangsari; Tri Agustina (Journal Research of Social Science, Economics, and Management, 2022)
Chronic kidney disease is a condition when kidney function fails gradually due to kidney damage. One of the causes of anemia in CKD is iron deficiency. Conventional oral iron treatment is not effective to treat iron deficiency anemia due to poor absorption and various side effects. Newer oral iron therapies with better tolerability and offer the potential to normalize iron without the need for intravenous iron. To review the currently available status oral iron therapies and summarizes the latest clinical trial evidence for their use. We researched Google Scholar and PubMed using keyword "iron" OR "ferri" OR "Ferro" OR "iron therapy" AND "Iron deficiency" AND "renal insufficiency, chronic" OR "chronic kidney disease" OR "kidney failure, chronic" OR "chronic renal disease" of last ten years. Total 8 articles recorded the identification stage by the criteria for inclusion. The articles are randomized controlled trials. Total 2.674 patients CKD of various types with or without anemia, age range 18-72 years were treated with oral iron therapies (ferric citrate, ferrous sulfate, sucroferric oxyhydroxide, ferric carboxymaltose) with varying doses. The most side effects of the therapies are gastrointestinal intolerance. Oral iron therapies are considered safe but drug development is still needed to minimize side effects.